An observational and cross-sectional study on prevalence of cognitive impairment and short-term changes in cognitive function after ischemic stroke in a tertiary care hospital - Pal, Anushree; Chakraborty, Durga Prasad; Mondal, Soumya Sarathi; Mandal, Mahadeb (Asian Journal of Medical Sciences, 2022)
Background: Stroke is a leading cause physical and cognitive disability. Aims and Objectives: The aims of this study were to investigate the prevalence and pattern of cognitive impairment (CI) after first-ever ischemic stroke. Materials and Methods: Sixty subjects with first-ever ischemic strokes, confirmed by magnetic resonance imaging (MRI), were selected. Their clinic-diagnostic and comorbidity data were collected. Mini mental state examination (MMSE) was done after 3–7 days on each patient. MRI was used to ascertain the side, vascular territory, extent, and neural tissues (cortical/subcortical) involved. CIs were categorized as normal, mild, and moderate-to-severe according to MMSE scores ≥ 24, 18–23, and 0–17, respectively. Data were summarized as mean±standard deviation (SD) for numerical variables and counts and percentages for categorical variables. Results: (1) Elderly (61–70 years), male and higher educated patients were more prevalent, hypertension (HTN) was the most common comorbidity. (2) Subcortical, middle cerebral artery (MCA), and anterior cerebral artery (ACA) lesions and non-dominant side involvement were common. (3) 80% patients had CI (65% mild and 15% moderate-to-severe). (4) CI was the most common in patients aged 71–80 years, of lower educational status and having both diabetes and HTN. MCA territory strokes and non-dominant side involvement resulted in more moderate/severe CI. (5) Registration followed by recall was least affected whereas language and praxis were more affected domains. Conclusion: Post-stroke cognitive decline is more common in elderly population and patients with lower education. CI is more in people with HTN and DM and in people with MCA territory infarct. Language and praxis were the most affected domain of all.